Jaccoud’s Arthropathy in Gout: An Unusual Association - Tayana Donato Alves; Isabela S. Oliveira; Luiza C. Fadul; Mittermayer B. Santiago (Case Reports in Rheumatology)
Jaccoud’s arthropathy (JA) is a deforming arthropathy observed mainly in patients with systemic lupus erythematosus. We report the case of a 41-year-old Brazilian man with a 10-year history of intermittent monoarthritis followed by bouts of polyarthritis affecting large and small joints. He presented deformities typical of JA and subcutaneous nodules. Histopathological findings of a nodule biopsy were consistent with gouty tophi. To our knowledge, this is the first report of JA secondary to chronic gout.